Better Household Surveys for Better Design of Infrastructure Subsidies - Gómez-Lobo, Andrés (World Bank, Washington, DC, 2012)
Reform of the water, electricity, and telecommunications sectors is gathering momentum in nearly all developing countries. Reform should include an assessment of whether subsidies are necessary and if so, how to design subsidies that reach their intended beneficiaries accurately and do not distort the market. A major challenge for reforming governments is to build the capability to do this fast enough for subsidy redesign to be incorporated in sector reform. Clearly, it would save time to use existing sources of information. Potentially, one of the most useful sources is the Living Standards Measurement Study (LSMS) survey. However, the LSMS questionnaires do not generate all the information needed for subsidy design. Fortunately, with a few simple and inexpensive changes, these surveys could be made much more useful for the design of subsidies and for devising policies that would give the poor better access to infrastructure services.